2015
DOI: 10.1007/s00213-015-4058-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of social deficits and repetitive behaviors in a mouse model of autism: the role of the nicotinic cholinergic system

Abstract: These findings support the hypotheses that the nicotinic cholinergic system modulates social and repetitive behaviors and may be a therapeutic target to treat behavior deficits in ASD. Further, the BTBR mouse may be valuable for investigations of the role of nAChRs in social deficits and repetitive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 55 publications
7
57
0
2
Order By: Relevance
“…Water intake, mouse weight, and nicotine plasma levels with nicotine doses examined here, have been previously reported in B6 and BTBR mice (Wang et al, 2015). We chose not to evaluate the effects of nicotine on nocifensive behavior in Fmr 1-KO mice because its effects (if any) on social behavioral deficits in the Fmr 1-KO strain have not been characterized.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Water intake, mouse weight, and nicotine plasma levels with nicotine doses examined here, have been previously reported in B6 and BTBR mice (Wang et al, 2015). We chose not to evaluate the effects of nicotine on nocifensive behavior in Fmr 1-KO mice because its effects (if any) on social behavioral deficits in the Fmr 1-KO strain have not been characterized.…”
Section: Resultssupporting
confidence: 65%
“…For example, in rats, acute nicotine administration is associated with an U-shaped dose response in complex cognitive tasks that require accurate time perception while in tasks that evaluate response rates, nicotine yields a bell-shaped dose-effect relationship (Popke et al, 2000). We had previously reported that nicotine administered over four weeks at doses used in the present investigation, also yielded non-linear dose-effect relationships on social and repetitive behaviors in the BTBR and B6 mice (Wang et al, 2015). Thus, the findings of a nonlinear pharmacodynamic profile of chronic nicotine on nocifensive behavior in BTBR and B6 mice are in keeping with our previous results and those of others(Picciotto, 2003; Popke et al, 2000).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations